Keterbacaan Buku Bahasa Arab Terbitan Pustaka Mulia - Nawawi, Mukshon; El Zahraa, Fatima; Yusufiyanti, Nurfatma Khumairo (Kalimatuna: Journal of Arabic Research, 2022)
This study aims to determine the level of readability of the Arabic teaching text book for sixth grade published by Pustaka Mulia and used in SD Islam Ruhama. The cloze test method was used to determine the level of readability of the text. The sample consisted of 80 students from the sixth grade of SD Islam Ruhama. The results of this study showed that the level of readability of the textbook varies. The readability level of the textbook is 34%, which means that the readability is at the level of frustration and the students' reading ability is 43%, which means the level of readability is at the instructional or educational level. The researchers concluded that the textbook did not meet the readability standards and that the readability of the textbook was varied. However, to further support students' reading skills, books or other additional references are still needed.